2018
DOI: 10.3389/fict.2018.00010
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Neurobiological Basis for Understanding Learning in University Modeling Instruction Physics Courses

Abstract: Modeling Instruction (MI) for University Physics is a curricular and pedagogical approach to active learning in introductory physics. A basic tenet of science is that it is a model-driven endeavor that involves building models, then validating, deploying, and ultimately revising them in an iterative fashion. MI was developed to provide students a facsimile in the university classroom of this foundational scientific practice. As a curriculum, MI employs conceptual scientific models as the basis for the course c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 76 publications
0
10
0
3
Order By: Relevance
“…Finally, the experimental group students identified the introduction of transdisciplinary contents in the proposal. The results showed that this effect did not contribute to a general conceptual change, but it did improve the context and the usefulness of the message as the correlation study revealed [18], activating the students' attention thanks to the brain interconnectivity necessary for conceptual learning [77], which facilitates assimilation, reasoning and acceptance [78].…”
Section: Discussionmentioning
confidence: 95%
“…Finally, the experimental group students identified the introduction of transdisciplinary contents in the proposal. The results showed that this effect did not contribute to a general conceptual change, but it did improve the context and the usefulness of the message as the correlation study revealed [18], activating the students' attention thanks to the brain interconnectivity necessary for conceptual learning [77], which facilitates assimilation, reasoning and acceptance [78].…”
Section: Discussionmentioning
confidence: 95%
“…Following the designs of cognitive training studies 35,36 , our study encompassed three phases: (1) the pre-training phase (day 1); (2) the home training phase (days 2–6); and (3) the post-training phase (day 7). The pre-training phase started with inviting participants to have their first MRI scan at CCNB.…”
Section: Methodsmentioning
confidence: 99%
“…Seguindo nos estudos com imageamento cerebral, destaca-se também o trabalho de Brewe e colaboradores, em 2018. Os autores usaram ressonância magnética funcional para investigar possíveis mudanças neuronais induzidas por uma determinada prática de aprendizagem ativa chamada "Modeling Instruction" [74]. Desenvolvida por Brewe (2008), trata-se de uma abordagem pedagógica que se fundamenta em uma característica específica da epistemologia científica, a modelagem [75].…”
Section: -Representações Algébricasunclassified